Fiqh Kankilo and the Purification System of the Butonese People: A Socio-Legal Historical Perspective of Islamic Law and Legal Pluralism - Alifuddin, Muhammad; Mahrudin, Mahrudin; Rosmini, Rosmini; Anhusadar, La Ode; Pratama, Finsa Adhi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This study is the dialectic between Islam and local culture in the purification system of the Butonese people. Data were obtained by means of interview, literature review, and observation. The study used the approaches of the social history of Islamic law and legal pluralism. The data were then analyzed using the Miles and Huberman analysis model. The findings of the study reveal that kankilo is a scientific concept that contains knowledge about the ways and purposes of purification as a result of the dialectic process between Islam and local traditions. For the Butonese, kankilo is taharah (purification), and taharah is kankilo. Hence, the concept and knowledge of taharah in the context of Buton culture can be referred to as Fiqh Kankilo. Fiqh Kankilo is a product of fiqh (Islamic jurisprudence) thought designed on the local characteristics of Buton society. The locality that is clearly visible in the content of Fiqh Kankilo is inevitable, considering that the quality of individuals and cultures where a religious law develops is not a blank slate or a cultural vacuum. Thus, religion (i.e., fiqh) and culture are ultimately two aspects that are certain to be in partnership, to build synergy, and to greet each other. This inevitability occurs because the understanding of religion cannot avoid the locality of culture that is relative and particular. The legitimacy of the existence of Fiqh Kankilo can at least be referred to the history of the development of Islamic legal thoughts, which provides room for accommodation of traditions on the paradigmatic basis of “adat al-muhakkamat” (customary law).